2015
DOI: 10.1192/pb.bp.113.044263
|View full text |Cite
|
Sign up to set email alerts
|

A memory clinic v. traditional community mental health team service: comparison of costs and quality

Abstract: Aims and method To compare the cost and quality of a memory-clinic-based service (MCS) with a traditional community mental health team (CMHT) service. Using a retrospective case-note review, we studied two groups, each with 33 participants. Consecutive referrals for diagnostic ‘memory’ assessments over 4 months were evaluated. Participants were evaluated for up to 6 months.Results The MCS was less costly than the CMHT service but the difference was not statistically significant (mean cost for MCS was £742, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 33 publications
3
27
1
2
Order By: Relevance
“…Our estimates of overall mean cost of supporting a patient for 6 months including and following initial assessment are higher than the £742 (2010/2011 GBP) reported by Rubinsztein et al (). That was a small study and appears to have excluded primary care contacts.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our estimates of overall mean cost of supporting a patient for 6 months including and following initial assessment are higher than the £742 (2010/2011 GBP) reported by Rubinsztein et al (). That was a small study and appears to have excluded primary care contacts.…”
Section: Discussionsupporting
confidence: 79%
“…The monthly cost of MAS in Croydon, including capital overheads, has been estimated at about £71 000 and £1200 per patient assuming 59 new patients a month (Curtis, 2014). Our estimates of overall mean cost of supporting a patient for 6 months including and following initial assessment are higher than the £742 (2010/2011 GBP) reported by Rubinsztein et al (2015). That was a small study and appears to have excluded primary care contacts.…”
Section: Comparison With Previous Researchcontrasting
confidence: 62%
“…Unlike previous studies focussing on a single memory clinic (9,13,28), our results are representative of MAS across all regions in the country (14). This economic evaluation is based on rigorous collection of data on different measures of effectiveness (both disease-specific and generic HQRL measures reported by patients and carers), and costs to the NHS, social care, carers and patients (adopting a societal perspective).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A previous study that focused on a single memory clinic (13) found no difference in costs of dementia services provided by MAS compared to community health services. The relative cost-effectiveness of MAS in England is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Stated grounds for providing an early diagnosis include enabling more timely access to appropriate treatment, information and support (Department of Health, 2015;Prince, Bryce & Ferri, 2011). There are an increasing number of case-finding initiatives based on clinical cognitive assessments in hospitals or in routine health checks (Hawkins, 2015;Rubinsztein et al, 2015), but for the majority of people early diagnosis relies on timely helpseeking and appropriate assessment within primary care.…”
Section: Introductionmentioning
confidence: 99%